Fluxes of angular momentum in a rotating layer with localized heat source - Evgrafova, Anna Valerievna; Popova, Elena Nikolaevna; Sukhanovskii, Andrey Nikolaevich (Computational Continuum Mechanics, 2016)
Fluxes of angular momentum in a rotating layer with localized heat source were studied by laboratory and numerical modeling. This study is motivated by the problem of tropical cyclogenesis. Despite decades of research, this problem is unsolved and attracts close attention of many scientific groups. It is known that the transport of angular momentum by meridional circulation is crucial for the formation of azimuthal flows. The transport of angular momentum, its sources and sinks essentially depend on initial and boundary conditions. The main goal of the study is to perform analyses of the transfer of angular momentum in a fluid layer and fluxes of angular momentum on solid boundaries for different values of governing parameters. The investigation was carried out experimentally and numerically. The experimental model is a cylindrical vessel with diameter of 15 cm. The model was placed on a rotating stand, which provided stable rotation in a wide interval of angular velocities. The depth of the layer was 3 cm, and different silicon oils were used as working fluids. Measurements of velocity fields were carried out by the PIV system “Polis”. Numerical calculations were done by CFD software FlowVision. Experimental and numerical results are in good agreement. It has been shown that the radial transport of angular momentum is of crucial importance for intensive cyclonic vortex formation. Intensive cyclonic vortex exists in a short interval of governing parameters. A decrease in viscosity and an increase in heating or angular velocity lead to the vortex asymmetry and further to its breaking. A detailed study of angular momentum transport by meridional circulation was carried out to describe vortex structure evolution. The locations of sources and sinks of angular momentum on solid boundaries were found. The structure of cyclonic vortex with decreasing viscosity was studied. It was shown that the instability of the vortex is strongly related to changes in the structure of a radial flow.